2014
DOI: 10.1016/j.jmpt.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic Use in the Medicare Population: Prevalence, Patterns, and Associations With 1-Year Changes in Health and Satisfaction With Care

Abstract: Objective The purpose of this study was to examine how chiropractic care compares to medical treatments on one-year changes in self-reported function, health, and satisfaction with care measures in a representative sample of Medicare beneficiaries. Methods Logistic regression using generalized estimating equations (GEE) is used to model the effect of chiropractic relative to medical care on decline in five functional measures and two measures of self-rated health among 12,170 person-year observations. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 44 publications
0
22
1
Order By: Relevance
“…In a study that found that most CIHS treatment for back and neck problems was provided by DCs, Martin et al used the Medicare Expenditure Panel Survey to compare costs of treatment for back and neck problems for patients who did and did not use CIHS: propensity scores for the 2 groups were used to match patients who had propensity scores within a ‘region of common support’ and then identify the ‘nearest neighbor’ as a method to develop 2 matched groups for comparison. 19 Weigel et al have applied inverse propensity score weighting to data from ‘Medicare Current Beneficiary Survey’ 20 respondents and to ‘Assets and Health Dynamics among the Oldest Old’ interviews 21 when comparing utilization and outcomes of chiropractic and conventional medical treatment of back pain in the Medicare population. However, to date, propensity score methods have not been applied directly to Medicare claims data to evaluate costs of care for patients seeking back pain treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In a study that found that most CIHS treatment for back and neck problems was provided by DCs, Martin et al used the Medicare Expenditure Panel Survey to compare costs of treatment for back and neck problems for patients who did and did not use CIHS: propensity scores for the 2 groups were used to match patients who had propensity scores within a ‘region of common support’ and then identify the ‘nearest neighbor’ as a method to develop 2 matched groups for comparison. 19 Weigel et al have applied inverse propensity score weighting to data from ‘Medicare Current Beneficiary Survey’ 20 respondents and to ‘Assets and Health Dynamics among the Oldest Old’ interviews 21 when comparing utilization and outcomes of chiropractic and conventional medical treatment of back pain in the Medicare population. However, to date, propensity score methods have not been applied directly to Medicare claims data to evaluate costs of care for patients seeking back pain treatment.…”
Section: Introductionmentioning
confidence: 99%
“…38 There is some evidence that individuals become accustomed to seeking chiropractic care, possibly because of lower satisfaction with medical care. 37,39,40 Our findings may indicate that chiropractic care may be used as a substitute for (rather than in addition to) medical care.…”
Section: Discussionmentioning
confidence: 81%
“…Among the Medicare population, chiropractic care may be beneficial in improving functional status among older adults. 3537 A provoking finding was that <10% of chiropractic users also use other medical services for the same episode of care. 38 There is some evidence that individuals become accustomed to seeking chiropractic care, possibly because of lower satisfaction with medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the recognition of the benefits of spinal manipulation in various government guidelines,107, 108, 109, 110, 111 the rise of the alternative health care movement, advances in the US military and Veterans Administration, and persistently high levels of patient satisfaction, 112 the chiropractic profession remains underrepresented in most discussions of health care delivery. Hopefully, a clarification of chiropractic’s identity and a greater unity of practitioners in delivering this message will help to rectify this problem.…”
Section: Discussionmentioning
confidence: 99%